Phenotype–environment correlations in longitudinal twin models - Beam, Christopher R. (Dev Psychopathol, 2013)
Gene–environment correlation (rGE) exists both within and between families. Between families, accumulating rGE has been used to explain dramatic changes in phenotypic means over time. The Dickens and Flynn model of increases in cognitive ability over generational time, for example, suggests that small changes in phenotype can lead to subsequent reallocation of environmental resources. This process sets up a reciprocal feedback loop between phenotype and environment, producing accumulating rGE that can cause large changes in the mean of ability, even though ability remains highly heritable in cross-sectional data. We report simulations suggesting that similar processes may operate within twin and sibling pairs. Especially in dizygotic twins and siblings, small differences in phenotype can become associated with reallocations of environmental resources within families. We show that phenotype–environment effects can account for age-related increases in rGE, rapid differentiation of siblings raised together, and widely reported increases in the heritability of behavior during childhood and adolescence.